Migration as cause and consequence of aspirations - Czaika, M; Vothknecht, M (International Migration Institute, 2012)
This paper aims to disentangle the relationship between aspirations and migration by analysing why Indonesian internal migrants generally have higher aspirations when compared with non-migrants. We ask whether migrants have higher aspirations for improving their economic well-being, and whether this 'capacity to aspire’ already existed before migration or is rather the result of the migration experience itself. Based on longitudinal information from three waves of the Indonesian Family and Life Survey (IFLS) between 1997 and 2007, we find robust evidence for migrants having higher individual aspirations than non-migrants already before they choose to migrate. About 70 per cent of the aspiration differential between future migrants and non-migrants can be explained by factors such as young age, education, or socio-economic background, which also affect the 'capacity to realise’ migration; the residual, however, is due to a personal trait, i.e. a certain disposition to have higher aspirations. Beyond these systematic pre-migration differences in aspirations, we find that despite the fact that migration is economically beneficial for most migrants, migration further spurs aspiration gaps.